THE SEPARATION OF CELLULOSE-BINDING DOMAIN FROM ENDOGLUCANASE EGL-II BY PROTEOLYSIS METHOD - Rina Masriani; Taufan Hidayat; Dewi Christanti Trisulo (JURNAL SELULOSA, 2013)
Protein molecule of endoglucanase Egl-II is consisted of two domains, namely cellulose-binding domain (CBD) which serves in promoting the adsorption of the enzyme to the insoluble crystalline cellulose and cellulase catalytic domain which is responsible for the hydrolysis reaction. In this study, CBD of endoglucanase Egl-II was separated from the intact protein by degradation using the papain and then separation by ultrafiltration methods. The CBD resulted can be used to modify the waste paper fibers. The results of electrophoresis before degradation showed that endoglucanase Egl-II has a molecular weight about 57.5 kDa. The electrophoregram after protein degradation and separation of CBD from the endoglucanase Egl-II showed that CBD was separated from the intact protein with a molecular weight about 21 kDa. The yield of CBDs were 59.51%. It can be concluded that CBD of endoglucanase Egl-II can be separated from the intact protein.Keywords: endoglucanase Egl-II, cellulose-binding domain, papain, ultrafiltration. ABSTRAKMolekul protein dari endoglukanase Egl-II terdiri dari dua domain, yaitu cellulose-binding domain (CBD) yang berfungsi untuk mempromosikan adsorpsi enzim ke selulosa kristalin dan domain katalitik yang bertanggung jawab dalam reaksi hidrolisis. Dalam studi ini, CBD dari endoglukanase Egl-II telah dipisahkan dari protein utuhnya setelah didegradasi dengan papain. Pemisahan CBD dari campuran hasil degradasi dilakukan dengan metode ultrafiltrasi. CBD yang dihasilkan dapat digunakan untuk memodifikasi serat kertas bekas. Hasil elektroforesis sebelum degradasi menunjukkan endoglukanase Egl-II memiliki massa molekul sekitar 57,5 kDa. Dari elektroforegram setelah degradasi protein dan pemisahan CBD dari endoglukanase Egl-II memperlihatkan bahwa CBD telah terpisah dari protein utuhnya dan memiliki massa molekul sekitar 21 kDa. Rendemen CBD adalah 59,51%. CBD dari endoglukanase Egl-II dapat dipisahkan dengan metode ini.Kata kunci: endoglukanase Egl-II, cellulose-binding domain, papain, ultrafiltrasi.